2015
DOI: 10.1016/j.leukres.2015.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell derived angiocrine support of acute myeloid leukemia targeted by receptor tyrosine kinase inhibition

Abstract: In acute myeloid leukemia (AML), refractory disease is a major challenge and the leukemia microenvironment may harbor refractory disease. Human AML cell lines KG-1 and HL-60 expressed receptors also found on endothelial cells (ECs) such as VEGFRs, PDGFRs, and cKit. When human AML cells were co-cultured with human umbilical vein endothelial cells (HUVECs) and primary bone marrow endothelial cell (BMECs), the AML cells were more resistant to cytarabine chemotherapy, even in transwell co-culture suggesting angioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 37 publications
(36 reference statements)
1
12
0
Order By: Relevance
“…In a complementary study, the abnormal secretion of these angiocrine factors potently inhibited the apoptosis of leukemia cells and promoted their growth via paracrine mechanisms [31]. However, inhibition of angiocrine receptors abrogated chemotherapy-induced angiogenesis and successfully reversed the resistance of AML [32].…”
Section: Bone Marrow Niche and Its Effects On Hematopoiesis And Leukementioning
confidence: 99%
“…In a complementary study, the abnormal secretion of these angiocrine factors potently inhibited the apoptosis of leukemia cells and promoted their growth via paracrine mechanisms [31]. However, inhibition of angiocrine receptors abrogated chemotherapy-induced angiogenesis and successfully reversed the resistance of AML [32].…”
Section: Bone Marrow Niche and Its Effects On Hematopoiesis And Leukementioning
confidence: 99%
“…Supporting this observation, another T‐ALL study showed a significant reduction in leukemia upon CXCL12 deletion from ECs , suggesting an important role for EC derived CXCL12 in leukemic survival. Studies have shown ECs to impart chemoresistance to AML cells in close proximity , while pharmacological inhibition of the endothelial cell derived angiocrine support significantly impeded leukemic growth . The work in aggregate shows that leukemia drastically affects the bone marrow compartment, changing both structural composition and function while hastening leukemic progression.…”
Section: Leukemia‐mediated Changes To Stromal Composition and Functionmentioning
confidence: 99%
“…PDGF is another important growth factor for angiogenesis under ischemia. It can be induced from ECs in response to ischemia or other stimulus 48 49 50 , which in turn activates medial SMCs proliferation and migration, leading to vessel wall remodelling 51 52 . During this process, XBP1 splicing plays an important role 17 .…”
Section: Discussionmentioning
confidence: 99%